2019
DOI: 10.1007/s10096-019-03676-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virulence factors related to the 30-day mortality of Klebsiella pneumoniae bacteremia at a tertiary hospital: a case–control study

Abstract: Purpose: Klebsiella pneumoniae bacteremia is a critical clinical presentation that is associated with high mortality. However, extremely few studies have investigated the virulence factors related to mortality of K. pneumoniae bacteremia in patients. The present study elucidated clinical and virulence factors associated with the 30-day mortality of K. pneumoniae bacteremia at a tertiary hospital. Methods: The medical records of 129 patients with K. pneumoniae bacteremia admitted to Osaka City University Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In a large prospective study investigating the main determinants for adverse outcome in patients with K. pneumoniae BSIs, the cytotoxicity pks gene cluster carriage by causative strains was an independent risk factor for 30-day mortality when accompanied by MDR [38]. Lastly, the siderophore-related iutA gene was found to be an independent predictor of the 30-day mortality in K. pneumoniae bacteremia [39]. However, almost all of these studies were conducted with pre-selected virulence genes searched by polymerase chain reaction (PCR) rather than sequencing the entire bacterial virulome.…”
Section: Discussionmentioning
confidence: 94%
“…In a large prospective study investigating the main determinants for adverse outcome in patients with K. pneumoniae BSIs, the cytotoxicity pks gene cluster carriage by causative strains was an independent risk factor for 30-day mortality when accompanied by MDR [38]. Lastly, the siderophore-related iutA gene was found to be an independent predictor of the 30-day mortality in K. pneumoniae bacteremia [39]. However, almost all of these studies were conducted with pre-selected virulence genes searched by polymerase chain reaction (PCR) rather than sequencing the entire bacterial virulome.…”
Section: Discussionmentioning
confidence: 94%
“…Most previous studies have reported that severity of underlying disease, intensive care unit (ICU) stay at infection onset, infection with extended-spectrum β-lactamase (ESBL)-producing or carbapenem-resistant KP (CRKP), and delayed administrations of appropriate therapy are the common risk factors for mortality in patients with KP BSIs ( Viale et al, 2013 ). Among the pathogenic factors, studies focusing on the virulence factors related to mortality in patients with KP BSI are scarce ( Kim et al, 2019 ; Namikawa et al, 2019 ). Kim et al indicated that carriage of the pks gene cluster was a relevant marker of early mortality using multivariate Cox hazards modeling ( Kim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al indicated that carriage of the pks gene cluster was a relevant marker of early mortality using multivariate Cox hazards modeling ( Kim et al, 2019 ). Another study of multivariate analysis showed that iutA was an independent predictor associated with increased 30-day mortality in patients with KP BSIs ( Namikawa et al, 2019 ). Notably, the virulence genes detected in previous studies were assessed by PCR, which may not fully address the clinically important genes influencing KP pathogenicity and virulence.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality reported in the literature ranges from 10.9% and 69.3%; this broad variation is in accordance with significant differences in the populations across the different studies included in terms of severity, need for ICU admission and percentage of strains with resistance mechanisms [ 46 , 47 , 48 ].…”
Section: Klebsiella Pneumoniae In Icus: Risk Factors and Out...mentioning
confidence: 61%
“…Predicted admission to the ICU was analyzed in 309 cases of bacteremia for K pneumoniae : 58 (18.8%) required ICU admission and only the pulmonary site revealed a clear association [ 49 ]. Several clinical issues have revealed a prognostic capacity for the following factors: female sex, age above 65, severity scales, use of corticosteroids, active neoplasia, severity of infection (sepsis/septic shock), respiratory site, gastrointestinal site other than the hepatobiliary system, need for mechanical ventilation and parenteral nutrition [ 47 , 49 , 50 , 51 ]. History of immunosuppression, high scores on prognostic scales and severity of infection are the most common factors with more overwhelming associations.…”
Section: Klebsiella Pneumoniae In Icus: Risk Factors and Out...mentioning
confidence: 99%